Farnesyl Diphosphate Synthase Inhibitors from In Silico Screening. (25th May 2013) - Lindert, Steffen; Zhu, Wei; Liu, Yi‐Liang; Pang, Ran; Oldfield, Eric; McCammon, J. Andrew
<x xml:space="preserve">Abstract</x> The relaxed complex scheme is an in silico drug screening method that accounts for receptor flexibility using molecular dynamics simulations. Here, we used this approach combined with similarity searches and experimental inhibition assays to identify several low micromolar, non‐bisphosphonate inhibitors, bisamidines, of farnesyl diphosphate synthase (FPPS), an enzyme targeted by some anticancer and antimicrobial agents and for the treatment of bone resorption diseases. This novel class of farnesyl diphosphate synthase inhibitors have more drug‐like properties than existing bisphosphonate inhibitors, making them interesting pharmaceutical leads.